1993
DOI: 10.1007/bf01088483
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolemic effect of amaranth seeds (Amaranthus esculantus)

Abstract: Hypocholesterolemic effect of amaranth seeds was studied in male wistar strain albino rats as against Bengal gram. The results showed that liver weights were significantly higher in animals with hypercholesterolemia inducing diet. Contrarily, weights of other organs like brain, kidney, testes and spleen showed higher weights with amaranth and bengal gram diets. Serum lipid and TG (triglyceride) contents were lower and HDL-cholesterol fraction was higher and comparable with amaranth seed diet. Feeding with amar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
11

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 11 publications
1
28
0
11
Order By: Relevance
“…The inclusion of certain components in the diet e.g. fish oil, sunflower, palm, soybean and flax oils, barley, oat bran, amaranth results in the drop of blood CHOL level (Chaturvedi et al, 1993;Qureshi et al, 1996;An et al, 1997;Grajeta, 1999;Castillo et al, 2000). This effect on CHOL level is ascribed to the presence of polyunsaturated fa�y acids (Skrivan et al, 2000;Newman et al, 2002), and in the case of amaranth it is due to the presence of tocotrienols and squalene or β-glucans (Qureshi et al, 1996;Kalač and Moudrý, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion of certain components in the diet e.g. fish oil, sunflower, palm, soybean and flax oils, barley, oat bran, amaranth results in the drop of blood CHOL level (Chaturvedi et al, 1993;Qureshi et al, 1996;An et al, 1997;Grajeta, 1999;Castillo et al, 2000). This effect on CHOL level is ascribed to the presence of polyunsaturated fa�y acids (Skrivan et al, 2000;Newman et al, 2002), and in the case of amaranth it is due to the presence of tocotrienols and squalene or β-glucans (Qureshi et al, 1996;Kalač and Moudrý, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…7,8) Diabetes is a major risk factor for premature atherosclerosis, and oxidative stress plays an important role. In fact, diabetic monocytes produce increased superoxide anion (O 2 Ϫ ).…”
Section: )mentioning
confidence: 99%
“…5) Recent studies have demonstrated a variety of important and unique nutraceutical type applications for grain amaranth, 6) including its use as an adjunct to lower blood glucose response in non-insulin-dependent diabetics and in other applications to lower blood serum cholesterol levels. 7,8) Diabetes is a major risk factor for premature atherosclerosis, and oxidative stress plays an important role. In fact, diabetic monocytes produce increased superoxide anion (O 2 Ϫ ).…”
mentioning
confidence: 99%
“…It is rich in protein, fat, dietary fi ber and minerals, especially calcium and iron, and contains a higher amount of lysine than conventional cereals [8] . Some studies with amaranth suggest that it exhibits a hypocholesterolemic effect [9,10] , and the cholesterol-lowering effect was attributed to the unsaturated fatty acids [9] or the fraction of fi ber other than the soluble portion [11] . Recently, we have reported that amaranth oil (AO) and squalene isolated from AO exhibited a marked cholesterol-lowering effect presumably via increased excretions of cholesterol and bile acid in hypercholesterolemic rats [12] .…”
Section: Introductionmentioning
confidence: 99%